13C Isotope Discrimination Variation in Guar [Cyamopsis tetragronoloba (L.) Taub.] Under Water-Deficit Conditions - Aurora Manley; Waltram Ravelombola; Curtis Adams; Rajan Shrestha; Philip Hinson; Calvin Trostle (International Journal of Plant Biology)
Guar is a legume cultivated for its high seed galactomannan content. India is the major guar producer globally and the U.S. has the largest guar market worldwide. Guar is drought-tolerant and suitable as a summer rotational crop in dryland farming systems. Studies have shown correlations between carbon δ13 isotope (C13) discrimination and water-use efficiency in other crops. The objective of this study was to assess the variation in carbon δ13 isotope discrimination among 30 guar accessions. Accessions were grown under greenhouse conditions in 3.79 L pots, including drought-stressed and well-watered treatments. For each accession, beginning at the V5–V8 growth stage, one pot was continuously irrigated, whereas irrigation was withheld from the other until wilting symptoms appeared after 50 days. Each treatment pair (well-watered/drought-stressed) was organized in a completely randomized design with three replications. Aboveground fresh and dry biomass data were collected, and the dry leaves were used for C13 isotope analysis. The results showed an increase in leaf C13 under drought stress. There were no differences among genotypes in C13 for well-watered plants (p = 0.63), but drought-stressed plants differed (p < 0.001). Significant positive correlations were identified between C13 under drought stress and the fresh (r = 0.70) and dry biomass (r = 0.68) of drought-stressed plants. These results demonstrate that C13 has potential as a criterion to identify drought-tolerant guar lines.